(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Ab initio molecular dynamics for the Zn-Al-Fe system were measured. The structural and electronic properties of Zn-Al-Fe alloy at different temperatures were simulated. Carried out the Partial Density of State (PDOS), Radial distribution function (RDF), coordination number, Mean square displacement (MSD) and diffusion coefficient of the Zn-Al-Fe system. The simulation results showed that Zn-Al-Fe alloys can be separated easily by vacuum distillation and the best condition was 1073K.